2019
DOI: 10.1016/j.jviromet.2019.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of respiratory viruses detected among hospitalized children with acute lower respiratory tract infections at Hospital Serdang, Malaysia

Abstract: Background: The role of respiratory viruses as the major cause of acute lower respiratory tract infections (ALRTIs) in children is becoming increasingly evident due to the use of sensitive molecular detection methods. The aim of this study was to use conventional and molecular detection methods to assess the epidemiology of respiratory viral infections in children less than five years of age that were hospitalized with ALRTIs. Methods: The cross-sectional study was designed to investigate the occurrence of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
1
8
2
Order By: Relevance
“…They showed that in uenza A was detected in 2.7% and 4.9% of included patients, respectively. However, our ndings were in contrast with those of Boivin et al [8]. These studies found that the prevalence of in uenza A virus in patients with respiratory tract infections was 21.6%, 31.7%, 15.7%, and 9.1%, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They showed that in uenza A was detected in 2.7% and 4.9% of included patients, respectively. However, our ndings were in contrast with those of Boivin et al [8]. These studies found that the prevalence of in uenza A virus in patients with respiratory tract infections was 21.6%, 31.7%, 15.7%, and 9.1%, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…In uenza B virus was not detected in our study. Globally, several studies reported that the frequency of in uenza B virus in respiratory tract infections was 0%, 11.9%, 3.2%, and 0.5%, respectively [8,7,5,1]. In the present study, the prevalence of adenovirus infection among military personnel was 1.4%.…”
Section: Discussionsupporting
confidence: 50%
“…There were 4 informants said that they got information about ARI treatment from their husbands or family members, while 2 others did not get any information about ARI treatment from their husbands or the family members. However, some mothers get information from their family members related to ARI treatment by bringing their children with ARI to a dukun (shaman) [5,15].…”
Section: Knowledge Variablementioning
confidence: 99%
“…The availability of health services supported by adequate facilities can give someone satisfaction in seeking treatment. The community considers health facilities that have incomplete/inadequate facilities cannot support the treatment process [8,15].…”
Section: Knowledge Variablementioning
confidence: 99%
“…During the winter season, viral respiratory tract infections are among the most common infections and can be severe in children, elderly, and immunocompromised patients, often leading to hospitalization. Fast and reliable laboratory testing is essential for patient management [1][2][3]. Many laboratories have developed multiplex qRT-PCR assays to detect respiratory viruses, but more recently also commercial PCR assays have become available.…”
Section: Introductionmentioning
confidence: 99%